Evaluation of the Results of Attitudes and Self-Efficacy of Middle School Students in Science Subjects - BUDIARTI, RETNI S; KURNIAWAN, DWI AGUS; TRIANI, ELZA; PERDANA, RAHMAT (Journal of Education Research and Evaluation, 2021)
This study aims to determine the differences and also the relationship between attitudes and self-efficacy of students in science lessons in each class VII at SMPN 2 Muaro Jambi. This type of research is quantitative with comparative type. The number of respondents used as a sample is 74 students. The data collection technique used simple random sampling. The results obtained using the T test, namely there are significant differences in the attitudes of students in science lessons, both female students and male students in class VII A and class VII B. From the results of the T test for self-efficacy, there are differences in self-efficacy.-efficacy of students in science lessons, both female students and male students in class VII A and class VII B. The results of the correlation test between attitudes and self-efficacy of students towards science subjects class VII A show that the two variables related. And the results of the correlation test in class VII B showed that the two variables tested were related, namely attitudes and self-efficacy.